Magnetic properties and FORC analysis of iron nanowire arrays. (December 2020) - Elmekawy, A.H.A.; Iashina, E.G.; Dubitskiy, I.S.; Sotnichuk, S.V.; Bozhev, I.V.; Napolskii, K.S.; Menzel, D.; Mistonov, A.A.
Abstract: Arrays of ferromagnetic nanowires are promising for diverse areas of practical application ranging from data storage to drug delivery. This makes it essential to study their magnetic behavior and magnetization reversal mechanisms. Here, we report on the fabrication of ordered hexagonal arrays of iron nanowires by templated electrodeposition with the use of porous anodic alumina templates. This technique made it possible to obtain nanocomposites with aligned nanowires of pure α -Fe that are stable against oxidation. The arrangement of the nanowires is revealed by small-angle X-ray scattering and scanning electron microscopy. Magnetic properties of the nanowire arrays are studied using first-order reversal curves (FORC) analysis supported by micromagnetic calculations and analytical models. Differences in the magnetic behavior of the arrays of nanowires, whose length varies by two orders of magnitude, are discussed. Experimental evidence of the antiparallel magnetization of the long nanowires in the array in low fields is demonstrated.